Journey of a woman through home, hearth and heart: a reading of Jaishree Misra’s ancient promises - Jose, Soumya; Raj, Sony Jalarajan (My University, 2012)
This paper endeavours to render a feminist reading to Ancient Promises. The article analyses how Janaki, a woman moulded according to the dictates of Manusmrithi emerges as a new empowered woman who controls her destiny. Janu disrupts the mould in which she has been created by the patriarchal society. The novel ends optimistically and the author's note in fact reveals the ultimate gift that Janu receives at the end as an ancient promise fulfilled.
Keywords: women; marriage; India; literary criticism